Splitting heirs: A study of the cell division site determinant MinD from the coccus Neisseria gonorrhoeae - Szeto, Jason (University of Ottawa (Canada), 2004)
Proper cell division site placement in the extensively studied rod Escherichia coli (Ec) is determined by the Min proteins. MinDEc recruits MinCEc to the membrane to inhibit cell division. MinEEc restricts MinCEc-MinDEc activity to cell pole regions by inducing MinDEc ATPase activity and causing it to dynamically oscillate from end-to-end in E. coli . The Dillon laboratory has identified min gene homologues in the coccus Neisseria gonorrhoeae (Ng) which, unlike E. coli, divides along two dimensions. This study investigates the role and identifies functional domains of gonococcal MinD (MinDNg). MinD is implicated in Neisseria gonorrhoeae cell division. Inactivation of minDNg dramatically disrupted N. gonorrhoeae division patterns and reduced cell viability. Overexpression of MinDNg and MinCNg together in the gonococcus inhibited cell division, producing grossly enlarged cells. MinDNg could complement an E. coli minD mutant and induced cell division arrest in this organism, provided endogenous E. coli MinC was present. GFP-MinDNg fusions also displayed MinENg-dependent oscillations within a coiled array in rod-shaped and round mutant E. coli. The self-interaction of MinDNg, as well as MinDEc, was detected using yeast two-hybrid assays, the first report of such interactions. Furthermore, size-exclusion chromatography and analytical ultracentrifugation showed purified MinDNg to be dimeric. MinDNg also interacted with both MinENg and MinC by yeast two-hybrid experiments. Structural and sequence alignments implicated a polar region, containing amino acids 92--94, in MinD dimerization. However, mutations to these residues did not eliminate interaction of MinDNg with itself, MinC, or MinE. Interestingly, this region may have a role in permitting bacterial MinD to respond to MinE stimulation, since mutant GFP-MinD fusions failed to oscillate from pole-to-pole in E. coli, despite being distributed uniformly within a coiled array. This was supported by in vitro assays, where MinENg was unable to stimulate the ATPase activity of mutated MinDNg. The conserved extreme N-terminus of MinDNg was also studied and shown to have a role in affecting MinDNg ATPase activity and localization dynamics. Successive truncation or mutation of this region affected MinDNg interaction with other Min proteins. Significantly, these alterations resulted in faster GFP-MinDNg oscillation cycles and increased tendencies to remain in the cytoplasm. Mutant MinDNg displaying this behaviour possessed hyper-ATPase activities independent of MinENg. This is the first study to characterize MinD from a naturally occurring coccus and demonstrates the protein acts as a cell division site determinant in N. gonorrhoeae and in E. coli. Results from this study were used to generate a model for N. gonorrhoeae cell division.
Keywords: Biology, Molecular.; Biology, Cell.; Biology, Microbiology.